The diagnostic accuracy of injury severity score and revised trauma score to predict mortality and hospital stay in polytrauma patients: A prospective cohort study. - Bhimani, Sagarkumar Pragjibhai; Nanda, Saurav N; Maharana, Niranjan; Mishra, Siddhartha (Student's Journal of Health Research Africa, 2025)
Background Trauma continues to be a significant global health concern, ranking as one of the leading causes of death and long-term disability worldwide. Each year, nearly 5 million individuals succumb to trauma-related injuries stemming from incidents such as road traffic accidents (RTAs), falls from height, violence, warfare, fires, and occupational hazards. Polytrauma is a leading cause of emergency admissions and mortality worldwide. Accurate trauma scoring systems like the Injury Severity Score (ISS) and Revised Trauma Score (RTS) help predict outcomes. Objectives- This study compares ISS and RTS in assessing mortality and hospital stay in polytrauma patients. Methods A prospective observational, cohort study was conducted from March 2023 to February 2025 at KIMS, Bhubaneswar, including 147 patients aged 18–60 with injuries to two or more body regions. ISS and RTS were calculated, and patients were grouped accordingly. Outcomes such as mortality and hospital stay were recorded. Statistical analysis was done using SPSS and GraphPad Prism with a significance level of p ≤ 0.05. Results Most patients were males (85.7%) aged 21–30 years, with road traffic accidents being the main cause (85.7%). Mean ISS was 25.07, and RTS was 10.59. Higher ISS and lower RTS were significantly associated with mortality (p < 0.0001). Age was also a significant predictor (p = 0.0053), while hospital stay did not differ significantly. Conclusion This prospective observational study highlights the clinical utility of the RTS and ISS as effective tools for predicting mortality and assessing injury severity among polytrauma patients. Recommendations It has been recommended that patients with RTS < 10 or ISS ≥ 20 should trigger senior review, expedited imaging, and ICU preparedness. Older patients, particularly those above 50 years, warrant heightened monitoring.